REKAYASA PEMBUATAN BALOK KAYU STRUKTURAL BERUKURAN BESAR DARI BALOK-BALOK KAYU BERUKURAN KECIL DENGAN PERKUATAN BAJA TULANGAN - Rochman, Abdul (Civil Engineering Forum Teknik Sipil, 2007)
At present, it is difficult to obtain the large size of wood beams, whereas the need to support heavy constructions is high. On the other hand, significant amount of small wood beams and log are available everywhere. Usually, these small wood beams and log are used to non-structural, or even for firewood. The objective of this study is to create a technology to made large structural wood beam by using the small wood beams. This study used 17 test models with the dimensions 40 mm x 90 mm x 1900 mm with the composition, 5 test beams made of whole mahoni (full section-BU), 6 test compiled wood beams made of 2 side layers (BS2BS), and 6 test compiled wood beams of 3 side layers (BS3BS). From those compiled beams made, three of them are made without strengthening, and the other three are given double steel bar strengthening using steel bar with the diamater is 8 mm. The result of this research shows that the load capacity of compiled wood beam increase significantly, i.e. about 87 % for BS2BS and 96% for BS3BS. The stiffness also increses as well, i.e. 79,4% for BS2BS and 90,5% for BS3BS. Therefore, it can proved technically, that it is possible to make big wood beam structure for heavy construction by using smaller dimension beams which has load capacity and performance is near with the whole beam.